Práticas de auditoria de desempenho em órgãos estaduais brasileiros de controle interno: elementos para configuração de um modelo - Nunes, Paulo Roberto de Carvalho (2006)
The practices of compliance audit tend limiting to the legal and normative aspects that regulate the actions, while the performance audit go more ahead, adding in the qualitative aspects of the management, in the results reached and in the impacts on the external environment. In the public area the performance audit is associated to the practices sheltered in the new public management and is exerted for about ten years for some Brazilian public institutions of control. The general objective of this work is to characterize the experiences of performance audit implemented by the Brazilian state agencies of internal control, seeking to identify elements for configuration of suitable model to the Brazilian context, contributing to consolidate experiences and concepts. The used methodology is characterized as qualitative, exploratory, descriptive, bibliographical and methodological, of field and the research accomplished under the form of case study, having been used script of half-directive interview as instrument of collection of data next to three Brazilian state agencies of internal control that exert this boarding for a long time. The result of the research allowed to conclude that the elements to be definite for configuration of a model of activities of performance auditing in the Brazilian state agencies of internal control are related to the need of definition of general guidelines for the activities of governmental audit, of establishment and consolidation of the institutional correspondent framework, of establishment of questions and answers to strategic aspects questions of implementation, qualification and competences of the auditors, of establishment of mutual reliable relation between the auditor and the company to be audited, the monitoring structuring process and evaluation of the reached results, of clarity with the relationship to the users of the accomplished works of performance audit, of identification e institutional maturity of the organ of internal control and characterization of the activities of performance audit.